Differentiating Stroke and Movement Accelerometer Profiles to Improve Prescription of Tennis Training Drills. Issue 3 (8th March 2023) - Perri, Thomas; Reid, Machar; Murphy, Alistair; Howle, Kieran; Duffield, Rob
Abstract: Perri, T, Reid, M, Murphy, A, Howle, K, and Duffield, R. Differentiating stroke and movement accelerometer profiles to improve prescription of tennis training drills. J Strength Cond Res 37(3): 646–651, 2023—This study compared the movement- and stroke-related accelerometer profiles and stroke counts between common on-court tennis training drills. Ten, junior-elite, male tennis players wore a cervical-mounted global positioning systems, with in-built accelerometer, gyroscope, and magnetometer during hard court training sessions ( n = 189). Individual training drills were classified into 8 categories based on previous research descriptions. Manufacturer software calculated total player load (tPL), while a prototype algorithm detected forehand (FH), backhands (BH), and serves and then calculated a stroke player load (sPL) from individual strokes. Movement player load (mPL) was calculated as the difference between tPL and sPL. Drill categories were compared for relative ( . min −1 ) tPL, sPL, mPL, and stroke counts via a 1-way analysis of variance with effect sizes (Cohen's d ) and 95% confidence intervals. Highest tPL . min −1 existed in accuracy and recovery or defensive drills ( p < 0.05), with lowest tPL·min −1 values observed in match-play simulation ( p < 0.05). For sPL·min −1, accuracy drills elicited greater values compared with all other drill types ( p < 0.05), partly via greater FH-sPL·min −1 ( p < 0.05), with lowest sPL·min −1 existing for match-play ( p < 0.05). Accuracy, open, and recovery or defensive drills result in greater BH-sPL·min −1 and BH . min −1 ( p < 0.05). Serve-sPL·min −1 is highest in technical and match-play drills ( p < 0.05). Higher mPL·min −1 existed in accuracy, recovery or defensive, 2v1 net, open, and 2v1 baseline ( p < 0.05). Furthermore, mPL·min −1 in points drills was greater than technical and match-play simulation drills ( p < 0.05). Higher hitting-based accelerometer loads (sPL·min −1 ) exist in accuracy drills, whereas technical and match-play drills show the lowest movement demands (mPL·min −1 ). These findings can aid individual drill prescription for targeting movement or hitting load.